Controlled Clinical Trials with Doping Substances in Sports Law - Deutsch, Erwin (Victoria University of Wellington Law Review, 2015)
The research ethics committee of a German medical university recently faced a totally new problem. The department for sports medicine had asked the committee to approve a protocol for a controlled clinical trial about the efficacy and safety of doping substances in cycling. This article considers the difficulties of the German law on this matter.